EMU and the renaissance of sovereign credit risk perception - Kai D. Schmid; Michael Schmidt (Institut für Angewandte Wirtschaftsforschung (IAW), 2012)
What is the role of fiscal variables for the assessment of sovereign credit risk? Has this role changed over time? In the face of the financial crisis many OECD countries have experienced large increases of government debt relative to GDP. This has triggered a distinct response of financial markets reflected by a sharp rise of longterm interest on government bonds. We show that, in particular, within some member countries of the European Monetary Union the explanation of investors' recent reactions to these fiscal imbalances is twofold: first, it is the worsening of fiscal positions due to the financial crisis that has been taken into account. Second, and more striking, it is financial markets' reconsideration of the role of these fiscal fundamentals for the pricing of sovereign credit risk. We argue that, from a historical perspective, this recent re-evaluation of fiscal positions seems little surprising. It is rather the re-establishment of the temporarily interrupted pricing of fiscal imbalances as a central factor of sovereign credit risk than the aggravation of fiscal imbalances. In our study we provide cross-country evidence for the impact of fiscal imbalances upon long-term interest rates. We use macroeconomic data from 1980 to 2012 and contrast a panel of 22 OECD countries with 11 EMU member countries and the so called GIIPS countries. This comparably long time span allows us to evaluate the changes in sovereign risk pricing that set in with the start of the EMU. In particular, we find that the relationship between the perceived default risk reflected by long-term interest rates and the public debt to GDP ratio as an indicator of fiscal sustainability is time regime as well as regional cluster specific. Our findings suggest that there is a strong connection of institutional aspects of EMU and the relationship between fiscal imbalances and changes in the pricing of sovereign credit risk.
Keywords: E43; E44; E62; 330; default risk; EMU; GIIPS; long-term interest rate; sovereign debt crisis